Unveiling the dynamic evolution of comparative advantage: assessing the competitiveness of China’s main winter and spring vegetable production regions - Hou, Dainan; Wang, Xin (Frontiers in Sustainable Food Systems, 2024)
This study assesses the competitive dynamics of vegetable production in China's principal winter-spring vegetable-producing regions, utilizing a perspective of dynamic comparative advantages. Drawing on statistical data from 2000 to 2018 on the development of the vegetable industry in these key provinces, our analysis incorporates methods such as the Resource Endowment Coefficient, the Comprehensive Comparative Advantage Index, the entropy method, and systematic cluster analysis to explore the evolution of competitive advantages in vegetable production across various provinces and cities. The findings reveal significant regional disparities in resource endowments and overall advantages in vegetable production during the winter and spring seasons. Notably, Chongqing, Hubei Province, and Shanghai exhibit a Resource Endowment Factor (EF) averaging above 1, indicating a relative abundance of production resources and a comparative advantage. Similarly, Hainan Province, the Guangxi Zhuang Autonomous Region, Guangdong Province, Fujian Province, Shanghai, and Zhejiang Province each demonstrate an average Comprehensive Advantage Index (AAI) exceeding 1, affirming their comprehensive comparative strengths. Overall, the competitiveness of vegetable production in these regions exhibits a fluctuating yet ascending trend, with notable disparities in competitive strengths across different areas. The ranking of annual average competitiveness scores in vegetable production is as follows: Shanghai > Zhejiang > Hubei > Hunan > Guangdong > Sichuan > Chongqing > Fujian > Guangxi > Jiangxi > Hainan > Yunnan. Based on these outcomes, the study proposes tailored strategic recommendations for provinces and cities according to their unique resource endowments and comparative advantages, aiming to enhance the sector's productivity and competitive stance.